Expert Consensus on ECG Identification Applied in the Insurance Industry - Zhongjian Li; Kangyin Chen; Shifeng Li; Tong Liu (Cardiovascular Innovations and Applications, 2023)
Electrocardiograms (ECGs) have the potential to be used as a reliable source of information for human identity recognition due to their universality, portability, and unique and stable biological identification features. This method enriches and refines existing biometric identification techniques, and is suitable for customer identity identification in the insurance industry. This article has the following objectives: 1) to introduce biometric identification techniques commonly used in the insurance industry, including ECG biometric identification techniques, and their advantages; 2) to discuss major aspects of ECG biometric identification techniques; 3) to systematically review the most recent advances in ECG identification and extraction characteristics from research in China and other countries; 4) to outline the technical aspects of using ECGs for recognizing client identity in the insurance industry; and 5) to discuss the future of ECGs in identity recognition. This article is aimed at further promoting the application of living personal ECG identification techniques in the insurance industry, and extending it to areas including medical insurance, banking, justice, public security, military, government, enterprises, and other departments and areas in which identification is needed to promote social stability and national security.